Differentiation of online text-based advertising and the effect on users' click behavior. (September 2015) - Jacques, Jason T.; Perry, Mark; Kristensson, Per Ola
Highlights: There is a drop in advertising click rates when using background coloration. There is a drop in content click rates when using background coloration. There is no difference in click rates when using unfamiliar differentiation. Abstract: Online syndicated text-based advertising is ubiquitous on news sites, blogs, personal websites, and on search result pages. Until recently, a common distinguishing feature of these text-based advertisements has been their background color. Following intervention by the Federal Trade Commission (FTC), the format of these advertisements has undergone a subtle change in their design and presentation. Using three empirical experiments, we investigate the effect of industry-standard advertising practices on click rates, and demonstrate changes in user behavior when this familiar differentiator is modified. Using three large-scale experiments ( N 1  = 101, N 2  = 84, N 3  = 176) we find that displaying advertisement and content results with a differentiated background results in significantly lower click rates. Our results demonstrate the strong link between background color differentiation and advertising, and reveal how alternative differentiation techniques influence user behavior.